The Effect of Import Tariff Policy on Indonesian Soybean Consumption and Production - Irada Sinta; Hasnah Hasnah; Dwi Yuzaria (International Journal of Agricultural Sciences, 2017)
This study aims to determine the factors affecting consumption and production of national soybean and the effect of soybean import tariff on domestic soybeanconsumption and production. This research was conducted in March - April 2017. The data used in this study is a secondary data in form of annual with a time series of 30 years ranged from 1986-2015. The result shows that the import quantity of soybean is affected by the variable of exchange rate; soybean consumption and import tariff. The price of imported soybean and exchange rate significantly affect domestic soybean price. While domestic soybean price and population significantly influence soybean consumption where a soybean productivity is highly responsive to wage rates. The simulation result shows that the quantity of imported soybean and soybean consumption increase with the tariff exemption (T = 0%) compared to condition when it is applied. Whereas, the domestic soybean price decreases at the exemption of tariffs compared to a condition when it is applied. Our study revealsthat the application of tariffs had no effect on soybean production and productivity.The result of forecasting without alternative tariff imports, which has been analysedduring the next 7 years, shows that in the next few years, Indonesia will not be able to achieve the self-sufficiency of soybeans.